1999
DOI: 10.1007/s007750050296
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of an extremenly sterically crowded monofunctional Pt complex, [Pt(1-MeC-N3)3(H2O)]2+ (1-MeC=1-methylcytosine), toward model nucleobases and selectivity toward guanine in single- and double-stranded deoxyoligonucleotides

Abstract: Reactions of [Pt(1-MeC-N3)3Cl]NO3 (1-MeC-N3 = 1-methylcytosine, bound to Pt via N3) and the respective aqua species [Pt(1-MeC-N3)3(H2O)]2+ with the model nucleobases 9-ethylguanine (9-EtGH), 9-methyladenine (9-MeA), single-stranded 5'd(T3GT3), and double-stranded [5'd(GA-GA2GCT2CTC)]2 have been studied in solution by means of 1H NMR spectroscopy, HPLC, and electrospray ionization mass spectrometry. Reactions are generally slow, in particular with the chloro species, and guanine is the only reactive base in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…It is not surprising, given the importance of Pt-based complexes in chemotherapy, that there have been a number of reports of the use of ESI-MS to examine the covalent attachment of platinum complexes to oligonucleotides (Wickham et al, 1995b;Gonnet et al, 1996b;Lowe et al, 1996;Troujman & Chottard, 1997;Janik et al, 1999;Kloster et al, 1999;Xu et al, 1999;Iannitti-Tito et al, 2000;). In one of our early studies, the binding of cisplatin to three self-complementary 6-mer oligonucleotides was examined (Wickham et al, 1995b).…”
Section: A Platinum Complexesmentioning
confidence: 96%
“…It is not surprising, given the importance of Pt-based complexes in chemotherapy, that there have been a number of reports of the use of ESI-MS to examine the covalent attachment of platinum complexes to oligonucleotides (Wickham et al, 1995b;Gonnet et al, 1996b;Lowe et al, 1996;Troujman & Chottard, 1997;Janik et al, 1999;Kloster et al, 1999;Xu et al, 1999;Iannitti-Tito et al, 2000;). In one of our early studies, the binding of cisplatin to three self-complementary 6-mer oligonucleotides was examined (Wickham et al, 1995b).…”
Section: A Platinum Complexesmentioning
confidence: 96%
“…There are, in principle, two more configurations of heterometal binding sets possible with 1: two cis-N' 2 O 2 as well as N' 3 (with pu 9-methyladenine and 9-ethylguanine) have in fact been prepared, yet with a different aim from the one raised herein. [36] Experimental Section Materials: [Pt(1-MeC-N3) 4 ](NO 3 ) 2 (1) [8] (from K 2 PtCl 4 and 1-MeC [37] ) was synthesized according to the literature. For the synthesis of the other complexes, see below.…”
Section: Resultsmentioning
confidence: 99%
“…In addition it is reported that hindered complexes are used for circumventing resistance by sterically inhibiting cellular detoxification by glutathione and other cellular thiols [36]. The presence of at least one leaving group in the synthesized complexes should allow the reaction with DNA, either for the cis and the trans complexes, as demonstrated in the literature [35].…”
Section: Discussionmentioning
confidence: 96%
“…The presence of thymine should help the binding between the metal complex and the nucleic acids, introducing an additional binding site and directing the complex also toward adenine containing sequences. The steric hindrance of the ligands should slow down the reaction rate with the DNA and probably affect the reaction mechanism and the selectivity for the binding sites [35]. In addition it is reported that hindered complexes are used for circumventing resistance by sterically inhibiting cellular detoxification by glutathione and other cellular thiols [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation